Quantitative Tracking of Salmonella Enteritidis Transmission Routes Using Barcode-Tagged Isogenic Strains in Chickens: Proof-of-Concept Study - Yang, Yichao; Ricke, Steven C.; Tellez, Guillermo; Kwon, Young Min (Frontiers in Veterinary Science, 2017)
Salmonella is an important foodborne bacterial pathogen, however, a fundamental understanding on Salmonella transmission routes within a poultry flock remains unclear. In this study, a series of barcode-tagged strains were constructed by inserting six random nucleotides into a functionally neutral region on the chromosome of S. Enteritidis (SE) as a tool for quantitative tracking of Salmonella transmission in chickens. Six distinct barcode-tagged strains were used for infection or contamination at either low dose (103 CFUs; 3 strains) or high dose (105 CFUs; 3 strains) in three independent experiments (Exp 1 oral gavage; Exp 2 contaminated feed; Exp 3 contaminated water). For all chick experiments, cecal and foot-wash samples were collected from a subset of the chickens at Days 7 or/and 14, from which genomic DNA were extracted and used to amplify the barcode regions. After the resulting PCR amplicons were pooled and analyzed by MiSeq sequencing, a total of approximately 1.5 million reads containing the barcode sequences were analyzed to determine the relative frequency of every barcode-tagged strain in each sample. In Exp 1, the high dose of oral infection was correlated with greater dominance of the strains in the ceca of the respective seeder chickens, and also in the contact chickens yet at lesser degrees. When chicks were exposed to contaminated feed (Exp 2) or water (Exp 3), there was no clear patterns of the barcode-tagged strains in relation to the dosage, except that the strains introduced at low dose required a longer time to colonize the ceca with contaminated feed. Most foot-wash samples contained only 1 to 3 strains for the majority of the samples, suggesting potential existence of a unknown mechanism(s) for strain exclusion. These results demonstrated the proof of concept of using barcode-tagged to investigate transmission dynamics of Salmonella in chickens in a quantitative manner.